AROC Pharm. Biotech. 2021
DOI: 10.53858/arocpb01013443
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility pattern of coagulase-negative staphylococci obtained from nares of adult patients admitted to Ahmadu Bello University Teaching Hospital (ABUTH), Zaria

Abstract: Coagulase-negative staphylococci (CoNS) are part of the normal microbial flora of the skin and mucous membranes. Nasal colonization with antibiotic-resistant CoNS represents both a risk factor for the colonized individual and their immediate contacts. This study determines the antibiotics susceptibility pattern and resistance phenotypes to a specific group of antimicrobial agents in CoNS isolate from the nares of adult patients from Ahmadu Bello University Teaching Hospital (ABUTH), Zaria, Kaduna State, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Atolagbe et al, 2021 reported (99.6%) resistance against Penicillin, (93.6%) against Ampicillin, and (63.2%) against Gentamicin. However, 100% sensitivity was observed in the case of Vancomycin [30].…”
Section: Discussionmentioning
confidence: 96%
“…Atolagbe et al, 2021 reported (99.6%) resistance against Penicillin, (93.6%) against Ampicillin, and (63.2%) against Gentamicin. However, 100% sensitivity was observed in the case of Vancomycin [30].…”
Section: Discussionmentioning
confidence: 96%
“…The standard formula was used to determine the minimum sample size using the p-value from prior studies, resulting in a total of 117 samples. Where N = Number of sample (sample size), Z = Standard normal deviate at 95% confidence interval=1.96, P = Prevalence from previous studies (8.3%) According to a study conducted at the Ahmadu Bello University Teaching Hospital (ABUTH), Zaria (Atolagbe et al, 2021), D = allowable margin of error = 0.05…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…0.1ml solution was spread to Petri plates containing sterilized nutrient agar and saboroud dextrose agar for bacterial and fungal isolation. The pure isolates were stored in bottles for further studies [25,26].…”
Section: Isolation Of Microorganismmentioning
confidence: 99%